Dynamic Stress Intensity Factor for Interfacial Cracks of Mode III Emanating from Circular Cavities in Piezoelectric Bimaterials - Li, D.; Wang, H.C.; Wu, L.X. (Проблемы прочности, 2016)
This paper investigates dynamic stress intensity factors in piezoelectric bimaterials with interfacial cracks emanating from the circular cavities under steady SH-waves. The interfacial cracks are assumed to be permeable. Green functions for the experiment were constructed through complex variable and wave function expansion methods. Based on the crack-division and conjunction techniques, a series of Fredholm integral equations of the first kind were established to calculate the stress intensity of the crack tips. Direct numerical integration was used to solve the equations. Some numerical results were plotted to indicate the influence of the defect geometry, material constants, and SH-wave frequencies on dynamic stress intensity factors.